The politics of newspaper operations in the Philippines the case of the Philippine Daily Inquirer during the Joseph Estrada administration. - Liwag, Vernice C.
This study sought to analyze the politics of newspaper operations in the Philippines focusing on the case of Philippine Daily Inquirer (PDI) during the Joseph Estrada Administration. The main research question of the study focused on how do the government, media operators, and advertisers affect the news operations of the Philippine DAily Inquirer during Joseph Estrada's term as president. The study attempts to situate the experience of PDI during the Estrada Administration using the Theories of the Press introduced by Frederick Siebert, Theodore Peterson, and Wilbur Schramm (1956). The theories used in the analysis are the Authoritarian theory, Soviet-Communist theory, and the social Responsibility theory. the study was conducted at the main office Philippine Daily Inquirer at Makati City. Seven journalists covering the Malacanang, Senate and House of Representatives beat and the Publisher of the Philippine Daily Inquirer participated in the study. The respondents were selected through purposive sampling. In-depth interviews access to electronic materials and library research of relatred literatures were used in gatherng the data needed. The data were then summarized, categorized, described and analyzed. Results of the study showed that this so-called media power cliques affected the news operations of the Philippine Daily Inquirer during the Estrada adminstration. There was adversarial relationship between Estrada and the Inquirer due to the critical reports that have been published in the Inquirer during his administration. The government did not use legal means. Respondents observed that the Philippine media environment is vulnerable to corruption and unethical practices. In the case of Inquirer, the respondents claimed that the media proprietors have no direct control over the treatment of news. However, because of the pressures exerted by the government abd advertisers in the newspapers, the proprietors have changed several news operation practices in the Inquirer. The Inquirer experienced a series of withdrawal of advertisement from the movie industry, several government institutions, as well as by business owned by people who have closed personal relationship with Joseph Estrada. The news operations of the Philippine Daily Inquirer were affected by the government no through the violation of any formal laws but by threatening the viability of the Inquirer as a business corporation. While the influences were coming from three different sources, it all emanated from the one source-the government. The study showed that in the case of the Philippine Daily Inquirer during the Estrada Adminstration the press was a fusion of authoritarian, libertarian, and social responsibility theories of the press in its structure, functions and relationship with the governement, owners, and advertisers. In conlcusion, the researchers argue that both the social and media systems in the Philippines are libertarian in orientation. However, in practice, authoritarian practices are present in the media, which can affect the news operations of a particular newspaper like the Inquirer.